2021
DOI: 10.1001/jamasurg.2020.6165
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fluoroquinolone Use With Short-term Risk of Development of Aortic Aneurysm

Abstract: IMPORTANCE Although fluoroquinolones are commonly prescribed antibiotics in the US, recent international studies have shown an increased risk of aortic aneurysm and dissection after fluoroquinolone use, leading to US Food and Drug Administration warnings limiting use for high-risk patients. It is unclear whether these data are true for the US population and who is truly high risk. OBJECTIVE To assess aortic aneurysm and dissection risks in a heterogeneous US population after fluoroquinolone use. DESIGN, SETTIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 28 publications
(53 reference statements)
1
56
1
6
Order By: Relevance
“…Dong et al conducted a nested case‐control study taking infections into account and found no association between FQ and a diagnosis of aortic aneurysm or dissection compared with other antibiotics and their corresponding indicated infections 27 . Lastly, Newton et al found in an observational study that the use of FQ was associated with an increased risk of a diagnosis of an aortic aneurysm compared with other antibiotics 28 …”
Section: Discussionmentioning
confidence: 99%
“…Dong et al conducted a nested case‐control study taking infections into account and found no association between FQ and a diagnosis of aortic aneurysm or dissection compared with other antibiotics and their corresponding indicated infections 27 . Lastly, Newton et al found in an observational study that the use of FQ was associated with an increased risk of a diagnosis of an aortic aneurysm compared with other antibiotics 28 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, vagus nerve dysfunction may then have the opposite effect: an increased rate of aneurysm development and rupture. Interestingly, a recent cohort study reported an increased rate of aneurysms at the level of the aorta, which is innervated by a branch of the vagus nerve [136], after use of FQs compared with alternative antibiotics, especially in adults 35 years or older [137].…”
Section: A Vulnerable Target: the Vagus Nervementioning
confidence: 99%
“…Для пациентов 18-44 лет частота развития аневризмы и диссекции аорты при терапии ФХ минимальна, в период от 45 до 64 лет -увеличивается в 4 раза и достигает пика у пациентов в возрасте от 65 лет и старше [5]. Анализ результатов ретроспективного когортного исследования, проведенного в США [8], свидетельствует о том, что в группе повышенного риска развития аневризмы аорты находятся лица старше 35 лет: для пациентов в возрасте 18-34 года относительный риск составил 0,99 (95% доверительный интервал (ДИ) 0,83-1,18), 35-49 лет -1,18 (95% ДИ 1,09-1,28), 50-64 года -1,24 (95% ДИ 1,19-1,28) при уровне статистической значимости р = 0,04. По данным популяционного продольного когортного исследования, проведенного в Канаде [12], общий относительный риск развития аневризмы аорты при терапии ФХ у пациентов старше 65 лет составил 2,72 (95% ДИ 2,53-2,93).…”
Section: клинико-морфологические формы и факторы риска поражения аорты при терапии фторхинолонамиunclassified
“…Риск поражения аорты возрастает с увеличением дозы и длительности применения ФХ [18]. Как правило, поражение аорты на фоне приема ФХ развивалось в течение 60-90 сут с начала терапии [2,8,9,19]. Согласно данным C. C. Lee и соавт., терапия ФХ в течение 3-14 сут приводила к возрастанию риска развития аневризмы и диссекции аорты в 2,41 раза, а дольше 14 сут -в 2,83 раза [15].…”
Section: клинико-морфологические формы и факторы риска поражения аорты при терапии фторхинолонамиunclassified
See 1 more Smart Citation